Paradoxes of Green : Landscapes of a City State - Doherty, Gareth (Book collections on Project MUSE., 2017)
"This highly innovative book is a multidisciplinary study of green and its significance from multiple perspectives: aesthetic, architectural, environmental, political, and social. It is centered on the Kingdom of Bahrain, the smallest and greenest of the Arab states in the Persian Gulf, where green has a long and deep history appearing cooling, productive, and prosperous--and a radical contrast to the hot, hostile desert. As is the case with cities around the world, green is often celebrated as a counter to gray urban environments, yet green has not always been good for cities. To have the color green manifested in arid environments is often in direct conflict with 'green' from an environmental point of view; this paradox is at the heart of the book. Given the resources required to maintain green in arid areas, including cities, the provision of green often bears significant environmental costs. In arid environments such as Bahrain, this contradiction becomes extreme and even unsustainable. Based on long-term ethnographic fieldwork, Gareth Doherty explores the landscapes of Bahrain where green represents a plethora of implicit human values and lives in dialectical tension with other culturally and environmentally significant colors and hues. The book's six chapters focus on: Blue, Red, Date-palm Green, Grass Green, Beige, and White. Implicit in his book is the argument that concepts of color and object are mutually defining and thus a discussion about green becomes a discussion about the creation of space and place"--Provided by publisher.